EFEKTIVITAS EKSTRAK BAWANG PUTIH (Allium sativum) DAN SIRIH (Piper betle) SEBAGAI BIOPESTISIDA TERHADAP HAMA PADA TANAMAN SAWI (Brassica juncea) SEBAGAI RANCANGAN LKPD MATERI BIOTEKNOLOGI SMA - Junaidi, Annajmu Sasna; Mahadi, Imam; Nursal, Nursal (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: Biopesticides are single active ingredients or compounds derived from plants (leaves, fruits, seeds or roots) functioning as repellents, pullers, antifertility (killers), killers and other forms, to control plant pest organisms (OPT). The basic ingredients used as biopesticides in this study are garlic (Allium sativum) and betel (Piper betle). This study aims to determine the effectiveness of garlic extract (Allium sativum) and betel nut (Piper betle) as a biopesticide against pests on mustard plants (Brassica juncea). This study uses a quantitative approach with a type of Completely Randomized Design (CRD) research. The results showed that the effective concentration in the use of biopesticides was at a concentration of 80% with the level of damage in the mild category and at the rate of 20%. The results of making garlic and betel nut extract can be used as one of the learning resources and learning media produced, namely in the form of LKPD (Student Worksheet).Key Words: Effectiveness of Biopesticides, Garlic and Betel Nut, and Mustard Greens